Target Development for the National Ignition Campaign. (1st February 2016) - Hamza, A. V.; Nikroo, A.; Alger, E.; Antipa, N.; Atherton, L. J.; Barker, D.; Baxamusa, S.; Bhandarkar, S.; Biesiada, T.; Buice, E.; Carr, E.; Castro, C.; et al.
Abstract: Complex and precise research targets are required for the inertial confinement fusion (ICF) experiments conducted at the National Ignition Facility. During the National Ignition Campaign (NIC) the target development team embarked on and completed a science and technology campaign to provide the capability to produce the required targets at the rate needed by the NIC. An engineering design for precision, manufacturing, and fielding was developed. This required new processes, new tooling, and equipment to metrologize and assemble components. In addition, development of new processing technology was also required. Since the NIC had to respond to new results from ICF experiments, the target development team had to respond as well. This required target designs that allowed for flexibility in accommodating changes in the targets for capsule dimensions and doping levels, hohlraum dimensions and materials, and various new platforms to investigate new physics. A continuous improvement of processes was also required to meet stringent specifications and fielding requirements.